2018
DOI: 10.18063/ijps.v4i2.817
|View full text |Cite
|
Sign up to set email alerts
|

Child trafficking in China: Evidence from sentencing documents

Abstract: Child trafficking has long been internationally recognized as a serious crime. However, due to data scarcity and inconsistent definitions, the scope and nature of such criminal activity are not well understood in China. To fill this gap, this study aims to provide new evidence by digitizing and analyzing sentencing documents on child trafficking in China during 2014-2016.Taking advantage of web scraping techniques, all child trafficking cases were downloaded from the China Judgments Online website. Through geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, after clarifying the concept of informal adoption, we used data from Chinese large-scale public welfare websites to analyze the spatiotemporal evolution and network characteristics of informal adoption. We found that giving children up for adoption was included in child trafficking in previous studies (Wang et al, 2018;Cai and Xin, 2019), which ignored the diverse roles of birth families in these processes. Therefore, the differences between true human trafficking and informal adoption deserve further exploration.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Therefore, after clarifying the concept of informal adoption, we used data from Chinese large-scale public welfare websites to analyze the spatiotemporal evolution and network characteristics of informal adoption. We found that giving children up for adoption was included in child trafficking in previous studies (Wang et al, 2018;Cai and Xin, 2019), which ignored the diverse roles of birth families in these processes. Therefore, the differences between true human trafficking and informal adoption deserve further exploration.…”
Section: Discussionmentioning
confidence: 84%
“…In China, the traditional idea of sons supporting parents in their old age and a son preference (Das Gupta et al, 2003;Liu, 2014a) were expressed in informal adoption because birth families wanted to give girls away. For child trafficking, boys are favored by adopting families (Li et al, 2017a(Li et al, , 2017bCai and Xin, 2019;Huang and Weng, 2019). This indicates that the gender distribution of informal adoption is determined by suppliers, while in child trafficking, gender preference is driven by the demand side.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations